2018
DOI: 10.25122/jml-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vitamin D and Postpartum Depression in Reproductive-Aged Iranian Women

Abstract: Background The aim of this study was to evaluate the relationship between vitamin D and postpartum depression in reproductive-aged Iranian women. Methods and Results This study was conducted on 120 women (60 with postpartum depression and 60 without) in Izeh, Iran. A socio-demographic questionnaire and Beck Depression Scale were used for data collection. The ELISA method was used for measuring 25-OH vitamin D (ng). The participants were classified according to their vitamin D level as follows: 25-OH-D < 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…[30] Many researchers have found that receptors of Vitamin D are primarily doled out throughout the brain of human, and its lack mutates neurotransmitters which are familiar to be included in of depression's symptoms. [12] Although the results of our study indicated a slight decrease in Vitamin D concentrations among the pregnant women who afterbirth affected by PPD; we found that the sera Vitamin D levels had no significant link between women with PPD and those with non-PPD (P = 0.6497), as shown in Table 1 [5,12,[31][32][33][34] they also found sera Vitamin D concentrations were significantly lower in depressed women than in the healthy subject. Similarly, the study Wang et al [35] did not record a considerable connect between depressive symptoms and low concentrations of Vitamin D through pregnancy.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[30] Many researchers have found that receptors of Vitamin D are primarily doled out throughout the brain of human, and its lack mutates neurotransmitters which are familiar to be included in of depression's symptoms. [12] Although the results of our study indicated a slight decrease in Vitamin D concentrations among the pregnant women who afterbirth affected by PPD; we found that the sera Vitamin D levels had no significant link between women with PPD and those with non-PPD (P = 0.6497), as shown in Table 1 [5,12,[31][32][33][34] they also found sera Vitamin D concentrations were significantly lower in depressed women than in the healthy subject. Similarly, the study Wang et al [35] did not record a considerable connect between depressive symptoms and low concentrations of Vitamin D through pregnancy.…”
Section: Discussionmentioning
confidence: 55%
“…[4] It is characterized by low appetite, fatigue, the feeling of guilt, and sleep problems. [5] Untreated maternal illness is potentially associated with adverse consequences for the mother, her infant, and her family. [6] The etiology remains unclear and complex.…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study of reproductive-aged Iranian women who had a venous blood sample taken 6-8 weeks after childbirth discovered an association between low vitamin D levels and PPD. (Abedi et al 2018).…”
Section: Studies With a Significant Association Between Vitamin D Lev...mentioning
confidence: 99%
“…The association between vitamin D levels and PPD is still conflicting. Several studies assumed that vitamin D deficiency might worsen PPD symptoms (Robinson et al 2014;Abedi et al 2018;Rouhi et al 2018;Pillai et al 2021;Amini et al 2022). A systematic review in 2019, including seven articles, reported that findings from six cohort studies suggest that vitamin D deficiency is associated with the incidence of PPD.…”
Section: Introductionmentioning
confidence: 99%
“…PMS can be caused by an assortment of causes, including hormone changes, sustenance, and lifestyle [1][2] . Females enduring from PMS are more likely to have picked up weight or experienced upsetting occasions within the past year [3][4][5] . Low Calcifediol levels are affected by dietary and/or behavioral changes in obese women 6 .…”
Section: Introductionmentioning
confidence: 99%